1976
DOI: 10.1242/jcs.22.3.607
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of myofibril growth and proliferation in fish muscle

Abstract: The mechanisms of myofibril growth proliferation were investigated in the red and white muscles of fish. In both types of muscle the ratio of lattice filament spacings between the Z disk and M line was found to be greater than that required for perfect transformation of a square into a hexagonal lattice. This mismatch was considered to result in the thin filaments being pulled obliquely instead of at right angles to the Z disk. The angle of pull of the thin filaments was measured in longitudinal sections. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…In both the leg and TDT muscles, sarcomere branches were more likely to occur near the cell periphery than in the interior (Supplementary Fig. 3c, d ) similar to previous findings in fish muscle 13 .…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In both the leg and TDT muscles, sarcomere branches were more likely to occur near the cell periphery than in the interior (Supplementary Fig. 3c, d ) similar to previous findings in fish muscle 13 .…”
Section: Resultssupporting
confidence: 87%
“…Sarcomere branching frequency has been shown to vary according to cell type 11 , 12 , though the mechanisms regulating the degree of connectivity have yet to be determined. Additionally, evidence of sarcomere branching can be seen in muscle images from fish 13 , chickens 14 , 15 , and frogs 16 in addition to mice 12 , 17 and humans 11 , 18 , 19 suggesting that myofibrillar networks may be conserved across vertebrate species. Conversely, insect fibrillar muscles, such as the commonly studied Drosophila indirect flight (IF) muscle, are known to be made up of the textbook individual myofibrils running the entire length of the muscle cell 20 22 , implying that a myofibrillar matrix may not occur in invertebrate muscles.…”
Section: Introductionmentioning
confidence: 99%
“…Given these conclusions, one is faced with the question of how an increase in mechanical loading induces myofibrillogenesis. As mentioned several times, one possibility is that the induction of myofibrillogenesis is mediated by hypertrophy and subsequent splitting of the pre-existing myofibrils (i.e., the myofibril splitting model) [21][22][23][24]. However, numerous studies have also described a different type of myofibrillogenesis that involves the de novo formation of myofibrils [60][61][62][63].…”
Section: Discussionmentioning
confidence: 99%
“…In support of his model, Dr. Goldspink published numerous images of single myofibrils that appeared to split into two smaller daughter myofibrils, as well as quantitative data which demonstrated that longitudinal splits usually occur in myofibrils that are significantly larger than myofibrils that do not contain splits [21-23]. Indeed, the model seemed so convincing that, when discussing how an increase in mechanical loading leads to the growth of muscle fibers, Dr. Goldspink concluded “The number of myofibrils increases ([25]), and this is almost certainly due to the longitudinal splitting of existing myofibrils rather than de novo assembly” [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation